Development and Assessment of a Simulator for in Vivo Confocal Microscopy in Fungal and Acanthamoeba Keratitis. (1st December 2020) - Roth, M.; Daas, L.; MacKenzie, C.R.; Balasiu, A.; Stachon, T.; Neumann, I.; Steindor, F.; Seitz, B.; Geerling, G.
ABSTRACT: Background and Purpose: In vivo confocal microscopy (IVCM) is a non-invasive imaging technique that allows morphological analysis as a diagnostic approach of the cornea in real time, thus providing a suspected diagnosis of fungal or amoebic keratitis immediately, whereas culture or PCR require several days or even weeks. Since these infections are rare, it is difficult for ophthalmologists to gain the experience necessary to differentiate infection from normal findings or artefacts. The purpose of this project was to establish a simulator, on which physicians could practice as well as acquiring a database of IVCM images of fungal or amoebic keratitis and respective analyses. Patients and methods: An IVCM simulator was set up with cadaver human corneas, infected with either acanthamoeba, candida or aspergillus. Twenty-one ophthalmologists were trained in IVC microscopy first in a Dry Lab, then practically on the simulator. For evaluation, the participants were asked to fill out a standardized questionnaire, with a pre- and post-course self-assessment. Results: The self-assessed theoretical and practical skills in differentiating infectious from non-infectious keratitis in IVCM significantly increased ( p = 0.0001, p = 0.0002, respectively). The barrier to use this technique decreased ( p = 0.0474). Conclusion: A very simple protocol based on a model of ex vivo corneal mycotic and amoebic infections can be used to train novices in the structured approach and diagnostic use of IVCM for corneal infections.